A community-based intervention programme on hormonal contraceptives: The utilisation of social networks - TOPUZOĞLU, AHMET; HIDIROĞLU, SEYHAN (TAYLOR & FRANCIS INC, 2016)
The aim of the study was to determine the effects of an intervention programme based on the utilisation of the social learning concept which is practised through social networks among adult women in a suburban population in Turkey. The study was performed in two disadvantaged neighbourhoods of Umraniye, Istanbul. One of the neighbourhoods served as the intervention while the other as the control group. In order to document the efficacy of the intervention, baseline and evaluation surveys were carried out in both neighbourhoods. The most widely known hormonal contraceptive method was oral contraceptives, while emergency contraceptives were determined as the least known methods. The improvement was higher for the least known methods. Education with peer groups is shown to be effective in improving the knowledge of women about contraception. Information transfer through peer groups should be used more frequently particularly for emergency contraception.
Keywords: Family planning methods; hormonal contraceptives; peers education; social network; EMERGENCY CONTRACEPTION; KNOWLEDGE; ATTITUDES; ISTANBUL